Efek Gosipol terhadap Kontraksi Usus Halus Mencit (Mus musculus) Swiss Webster Jantan secara in vitro - Darmadi Goenarso; Suripto Suripto; Zulfiani Zulfiani (Jurnal Matematika & Sains, 2004)
The in vitro effect of gossypol on the small intestinal contractility of Swiss Webster mice have been examined. Thirty six sexually mature male mice with body weights of 30,5-36,5 g. were used and the tested concentrations of gossypol were 5, 7.5, and 10 ppm. Segments of the small intestine such as: duodenum, jejunum and ileum were isolated and immersed in Tyrode solution at 37 oC. The contractions of these organs were measured and recorded using a myograph and physiograph. As control, the contractions of these organs were recorded in Tyrode solution for 360 seconds. The solution was then replaced by gossypol-Tyrode solution and the contractions were recorded again for the next 360 seconds. The results showed that gossypol increased shortly and followed by gradual decreases of tension in all small intestinal segments. Gossypol also lowered the frequency of the intestinal contractions when compared with control. The strongest action of gossypol was found when the intestines were treated in 10 ppm, compared to the action of those treated with 7.5 ppm and 5 ppm. It is assumed that gossypol impaired peristaltic movements of the intestines and thus decreased digestibility of mice.